Automatic Management: A Forecast and its Educational Implications - Ackoff, Russell L. (Management Science, 1955)
These remarks are intended to outline a forecast of the future of management and management science, namely that through scientific research management is going to become increasingly automatic. This forecast is based on a survey and projection of some contemporary technological and scientific developments.